Persistent Staphylococcus aureus isolates from two independent bacteraemia cases display phenotypic traits that increase in vivo bacterial fitness and immune evasion - Ben Pascoe (Infection and Immunity, 2015)
Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) are a leading cause of healthcare- and community-associated infections and remain a serious clinical threat. S. aureus bacteraemia is further complicated by the phenomenon of treatment failure and persistence despite confirmed in vitro susceptibility of the infecting strain to the administered antibiotics. In this study isolates originating from two individual cases of persistent S. aureus bacteraemia (PB) were analysed alongside isolates from three cases of resolved bacteraemia (RB) in order to identify traits exclusively associated with persistence.Persistent isolates from both cases showed the same novel virulence traits which were not exhibited by matching initial isolates or by RB isolates. Interestingly, these persistence-associated characteristics did not include two well-described persistence mechanisms, i.e. the presence of small colony variants (SCV) and/or increased intracellular host cell persistence. When compared to their cognate initial isolates, both sets of persistent isolates displayed growth advantages in nutrient-poor medium and showed increases, as analysed by iTRAQ LC-MS, in SaeRS regulated proteins which are involved in immune evasion, host cell adhesion and stress response systems (Map1/Eap, Emp, Sbi, Csp and Trx). Additionally, the persistent isolates displayed improved glucose mediated biofilm formation, had attenuated virulence using a Galleria mellonella virulence model, showed differential sensitivity to external stressors and had daptomycin non-susceptibility. Whole genome sequence comparisons identified several different gain-of-function (GoF) single nucleotide polymorphisms (SNP) in the mprF gene in the sequential isolates of both cases of S. aureus persistent bacteraemia, suggesting a significant role for MprF function during development of S. aureus persistence.